2022
DOI: 10.1021/acsami.2c11317
|View full text |Cite
|
Sign up to set email alerts
|

Rose-like VS2 Nanosheets Chemically Anchored on Carbon Nanotubes for Flexible Zinc-Ion Batteries with Enhanced Properties

Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) are an attractive alternative for flexible energy storage devices due to their excellent safety and low cost. One of the main challenges that plagues their practical applications is the restricted variety of cathode materials with fast reaction kinetics and good mechanical properties. Herein, we prepared rose-like VS2 nanosheets which have decent specific capacities, metallic conductivity, and open-enough channels and further incorporated them into a single-walled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…In addition, it shows stable energy storage in aqueous zinc-ion flexible energy storage equipment. 89 In addition, doping heteroatoms (usually nitrogen, N) can improve the reaction activity of carbon, and the high affinity of doped N for transition metals (TMs) can form a strong coupling with vanadium-based compounds, showing extraordinary electrochemical performance. 188−192 As an example, Liu et al prepared shuttle-like VS 2 nanocrystals grown on the layer of N-doped carbon.…”
Section: Challenges and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it shows stable energy storage in aqueous zinc-ion flexible energy storage equipment. 89 In addition, doping heteroatoms (usually nitrogen, N) can improve the reaction activity of carbon, and the high affinity of doped N for transition metals (TMs) can form a strong coupling with vanadium-based compounds, showing extraordinary electrochemical performance. 188−192 As an example, Liu et al prepared shuttle-like VS 2 nanocrystals grown on the layer of N-doped carbon.…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…The single-walled nanotube network provides a good conductive network and avoids the stacking of VS 2 nanosheets. In addition, it shows stable energy storage in aqueous zinc-ion flexible energy storage equipment …”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Aqueous rechargeable energy storage (ARES) mainly including aqueous ion batteries, aqueous supercapacitors, and aqueous ion capacitors has been considered as a promising complement to the commercially energy storage technologies based organic electrolytes due to their cost-effectiveness and high safety. [1][2][3][4] However, the intrinsic weakness of frequently being frozen of aqueous electrolytes reduces their low-temperature adaptability and cannot fulfill the requirements of human activities expansion, such as polar research, outdoor exploration, high-altitude region expedition, and military action, which require efficient and sustainable power supply under extreme environment. [5][6][7] In addition, electrochemical impedance spectroscopy revealed that both the solution resistance and charge transfer resistance deteriorated rapidly when the operation temperature was near to its freezing point, resulting in inevitable performance atom (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, layered vanadium-based compounds (VCs) have been demonstrated to own fascinating energy storage properties as cathode materials in the AZIB system by both theoretical predication and experimental realization. As one member of the VCs, vanadium disulfide (VS 2 ) has been synthesized and exploited extensively as a host material in storage of zinc ions owing to its layered architecture and large interlayer spacing of 0.576 nm. ,, However, the stacked structures of layered VS 2 always confine the convenient diffusion of electrons and ions in a two-dimensional (2D) plane, impeding their rapid transport between cathodes and anodes, especially at high currents. As another member of VCs, vanadium tetrasulfide (VS 4 ) crystal has a one-dimensional (1D) atomic chain architecture composed of tetravalence vanadium ions coordinated with S 2 2– dimes.…”
Section: Introductionmentioning
confidence: 99%
“…The low electrical conduction, sluggish ion diffusion dynamics, morphology agglomeration, structural collapse, and solubility in aqueous electrolytes during repeated charge and discharge procedures lead to an unsatisfactory electrochemical real performance of VCs, which greatly impedes its further application in AZIBs. Accordingly, efficient reliable routes including construction of a micro/nano-structure and introduction of carbonaceous materials with excellent mechanical and conductive properties have been taken to deal with the aforementioned drawbacks. ,, At present, several carbonaceous materials have been used to compound with VC micro/nano materials to meliorate their energy storage performance. ,, Among them, graphene has drawn considerable concerns thanks to its distinct physicochemical properties. Nevertheless, in view of the existence of π–π interactions and strong van der Waals working force in the graphene nanolayers, their aggregation and restack occurred frequently, resulting in the inheritance of a graphite nature. , This is unfavorable for the utilization of graphene on high-performance energy storage systems.…”
Section: Introductionmentioning
confidence: 99%